Interfacial strength and debonding mechanism between aerogel-spun carbon nanotube yarn and polyphenylene sulfide. (September 2016) - Shao, Yiqin; Xu, Fujun; Li, Wei; Zhang, Kun; Zhang, Chunyang; Li, Ranxing; Qiu, Yiping
Abstract: The interfacial bonding properties between the carbon nano-tubes yarn and polyphenylene sulfide are investigated using the micro-bond test. Carbon nano-tubes yarn fabricated by floating catalyst chemical vapor deposition with a high Poisson's ratio of 3.5, and high-performance thermoplastic resin polyphenylene sulfide are used as matrix. In order to improve the tensile strength of the yarn so as to get sufficient data points for the micro-bond test for interfacial bonding strength, a pretreatment that combines drafting and dichloromethane shrinking processes is applied. The pretreated carbon nano-tubes yarn shows a 23% increase in tensile strength (from 117 to 144 MPa) and a 260% increase in initial Young's modulus (from 0.8 to 3.2 GPa). The effective interfacial shear strength is calculated to be 13.1 MPa and analyzed based on fracture mechanism of a mixed failure mode.